Accurate Diagnosis of Schistosoma mansoni and S. haematobium from Filtered Urine Samples Collected in Tanzania, Africa - Koreena Miller; Javeriya Choudry; El Shaimaa Mahmoud; Nilanjan Lodh (Pathogens, 2024)
Schistosomiasis is a bloodborne, and waterborne parasitic disease caused by the human Schistosoma species, namely Schistosoma mansoni and S. haematobium. The parasite requires an intermediate snail host, where they grow and develop, along with a human host (definitive). Schistosoma egg detection in feces (S. mansoni) and urine (S. haematobium) are the WHO-recommended confirmatory diagnostic tests. The goal of our research was to determine the efficacy of detecting single or dual Schistosome species from filtered human urine samples collected in Tanzania by amplifying species-specific cell-free repeat DNA fragments via polymerase chain reaction (PCR) and gel electrophoresis. In total, 104 filtered human urine samples were evaluated and collected from individuals residing in the village of Kayenze, Tanzania. All samples were detected with 100% accuracy and no cross-amplification was present. For a single infection of S. mansoni, 22 (21%) of the samples were positive, while 15 (14%) of the samples were negative via PCR. Moreover, for a single infection of S. haematobium, 7 (7%) of the samples were positive, while 15 (14%) of the samples were negative. Dual infections were found in a higher percentage, with 60 (58%) of the samples being positive. Thus, we have justified that PCR is more sensitive and specific by amplifying species-specific cell-free repeat DNA fragments from the same urine sample than WHO-recommended methods of processing stool and urine.